Recovery of degraded areas using topsoil in the Amazon rainforest - Ribeiro, A. I. [UNESP]; Longo, R. M.; Melo, W. J.; Lourenço, Roberto Wagner [UNESP]; Maciel, A. J S; Rosa, André Henrique [UNESP]; Fraceto, L. F. [UNESP] (WITPRESS LTD., 2012)
This study is aimed at evaluating the effect of placing the top soil cover areas, such as tailings degraded by tin mining, in the Amazon rainforest in Brazil. The evaluations of the planting sites occurred in areas where tin mining was carried out, basically planting native trees over a period of seven years. This work did not come from a pre-decreed methodology of experimental design, and data was collected only seven years after planting. Thus, it was not possible to identify all variables that contributed to a better recovery of the areas. Sampling was done about seven years after placing the top soil and is determined: pH, organic matter content, P, K, Ca, Mg, Al, cation exchange capacity (T), base saturation (V%), B, Fe, Zn, Cu and Mn. The native forest species existing at the site were evaluated in relation to height (in meters) and diameter of the base. For all sites where the surface layer of soil was applied, there were significant differences in the growth of native species. A fundamental aspect in the rehabilitation of areas degraded by mining, in general, is the knowledge about the soil where that recovery must be conducted. The specific procedures in the rehabilitation of those areas depend essentially on the physical, chemical, biological and mineralogical properties of the soil, which must present conditions for the adequate development of the plants. The initial idea of implanting a project of recovery of soils degraded by mining in the Amazon Forest emerged from a first visit to the field, carried out in 1998. The conditions of the already mined areas, in comparison to the exuberant forest of the surroundings caught our attention. The mining company that acts in the area had already been trying for some time to implant a plan of recovery of these mining areas, however without reaching any significant positive results. The loss of organic matter is one of the main problems of degraded areas in Brazil. The storage and reuse of a blanket of soil (topsoil) produce excellent results, but most of the miners consider this technique expensive and difficult because of operational costs and the sharp topographical condition of the mine site. Therefore, a research project was elaborated prioritizing the recovery of the soil degraded by the tin mining as a prior step to the recovery activities with native forest species. The formation of a superficial pseudo-horizon that supported the vegetation and the time that it would take for its establishment became the main objective of this research. The objective of this work is to verify the levels of elements and their traces in areas where top soils were applied for the remediation of degraded areas with local re-vegetation. © 2011 WIT Press.
Keywords: anthropogenic effect; human activity; land degradation; mining; rainforest; recovery plan; topsoil; Amazonas [Brazil]; Brazil